A guide to programming logic and design - Farrell, Joyce (Cambridge, Mass. ; London : Course Technology, 1999)
An overview of computers and logic. Structure. Modules, hierarchy charts, and documentation. Writing a complete program. Making decisions. Looping. Control breaks. Arrays.
Keywords: Computer; Logic; Structured programming; Logic programming; Logic design